The β2Tubulin, Rad50-ATPase and enolase cis-regulatory regions mediate male germline expression in Tribolium castaneum - Sher Afzal Khan (Nature Portfolio, 2021)
Abstract Genetics-based pest management processes, including the sterile insect technique, are an effective method for the control of some pest insects. However, current SIT methods are not directly transferable to many important pest insect species due to the lack of genetic sexing strains. Genome editing is revolutionizing the way we conduct genetics in insects, including in Tribolium castaneum, an important genetic model and agricultural pest. We identified orthologues of β2Tubulin, Rad50-ATPase and enolase in T. castaneum. Using RT-PCR, we confirmed that these genes are predominantly expressed in the testis. PiggyBac-based transformation of T. castaneum cis-regulatory regions derived from Tc-β 2 t, Tc-rad50 or Tc-eno resulted in EGFP expression specifically in the T. castaneum testis. Additionally, we determined that each of these regulatory regions regulates EGFP expression in different cell types of the male gonad. Cis-regulatory regions from Tc-β 2 t produced EGFP expression throughout spermatogenesis and also in mature sperms; Tc-rad50 resulted in expression only in the haploid spermatid, while Tc-eno expressed EGFP in late spermatogenesis. In summary, the regulatory cis-regions characterized in this study are not only suited to study male gonadal function but could be used for development of transgenic sexing strains that produce one sex in pest control strategies.